FBXW7 deletion contributes to lung tumor development and confers resistance to gefitinib therapy. Issue 6 (9th May 2018) - Xiao, Yi; Yin, Chunli; Wang, Yuli; Lv, Hanlin; Wang, Wenqing; Huang, Yurong; Perez‐Losada, Jesus; Snijders, Antoine M.; Mao, Jian‐Hua; Zhang, Pengju
Abstract : Gefitinib, an epidermal growth factor receptor–tyrosine kinase inhibitor (EGFR‐TKI), is an effective treatment for non‐small‐cell lung cancer (NSCLC) with EGFR activating mutations, but inevitably, the clinical efficacy is impeded by the emergence of acquired resistance. The tumor suppressor gene FBXW7 modulates chemosensitivity in various human cancers. However, its role in EGFR‐TKI therapy in NSCLC has not been well studied. Here, we demonstrate that the mice with deficient Fbxw7 have greater susceptibility to urethane‐induced lung tumor development. Through analysis of The Cancer Genome Atlas data, we show that deletion of FBXW7 occurs in 30.9% of lung adenocarcinomas and 63.5% of lung squamous cell carcinomas, which significantly leads to decrease in FBXW7 mRNA expression. The reduction in FBXW7 mRNA level is associated with poor overall survival in lung cancer patients. FBXW7 knockdown dramatically promotes epithelial–mesenchymal transition, migration, and invasion in NSCLC cells. Moreover, with silenced FBXW7, EGFR‐TKI‐sensitive cells become resistant to gefitinib, which is reversed by the mammalian target of rapamycin inhibitor, rapamycin. Furthermore, xenograft mouse model studies show that FBXW7 knockdown enhances tumorigenesis and resistance to gefitinib. Combination of gefitinib with rapamycin treatment suppresses tumor formation of gefitinib‐resistant (GR) FBXW7‐knockdown cells. In conclusion, our findings suggest that loss of FBXW7 promotes NSCLC progression as well as gefitinib resistance and combination of gefitinib and rapamycin may provide an effective therapy for GR NSCLC. Abstract : The role of tumor suppressor gene FBXW7 in EGFR‐TKI therapy in non‐small‐cell lung cancer (NSCLC) has not been well studied. Here, we demonstrate that FBXW7 knockdown promotes NSCLC progression as well as gefitinib resistance by activating the mTOR/p70S6K pathway both in vitro and in vivo . A combination of gefitinib and rapamycin may provide an effective therapy for gefitinib‐resistant NSCLC.